The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1051/0004-6361/201321386
|View full text |Cite
|
Sign up to set email alerts
|

Evolution induced by dry minor mergers onto fast-rotator S0 galaxies

Abstract: Context. Numerical studies have shown that the properties of the S0 galaxies with kinematics intermediate between fast and slow rotators are difficult to explain by a scenario of major mergers. Aims. We investigate whether the smoother perturbation induced by minor mergers can reproduce these systems. Methods. We analysed collisionless N-body simulations of intermediate and minor dry mergers onto S0s to determine the structural and kinematic evolution induced by the encounters. The original primary galaxies re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 115 publications
4
34
0
Order By: Relevance
“…However, here we would like to point out that, whatever that contribution has been, any S0s deriving from the major merger between two spirals would also contribute to the trend observed by Dressler of transformation of spirals into S0s. It is beyond the scope of the present paper to quantify the relevance of major mergers in terms of creating S0s (recent estimates indicate that they may have been essential in the buildup of ∼50% of present massive S0s at most, see Tapia et al 2014), but it is a mechanism that surely needs to be taken into account, and may especially explain the origin of the S0s that reside in groups and less dense environments. S0s are at least as common in groups as in clusters, and galaxy interactions are the dominant evolution mechanism in this regime (Wilman et al 2009;Mazzei et al 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, here we would like to point out that, whatever that contribution has been, any S0s deriving from the major merger between two spirals would also contribute to the trend observed by Dressler of transformation of spirals into S0s. It is beyond the scope of the present paper to quantify the relevance of major mergers in terms of creating S0s (recent estimates indicate that they may have been essential in the buildup of ∼50% of present massive S0s at most, see Tapia et al 2014), but it is a mechanism that surely needs to be taken into account, and may especially explain the origin of the S0s that reside in groups and less dense environments. S0s are at least as common in groups as in clusters, and galaxy interactions are the dominant evolution mechanism in this regime (Wilman et al 2009;Mazzei et al 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Mergers that differ only slightly in their initial conditions are capable of producing quite different sort of remnant systems, and all of them with bulge-disc structural coupling consistent with observations. If we also account for the observational and computational evidence that points to a merger origin for a significant fraction of S0s (and in particular, for the most massive ones, see Eliche-Moral et al 2010a;Bernardi et al 2011a,b;Méndez-Abreu et al 2012;Barway et al 2013;Wilman et al 2013;Tapia et al 2014), it seems unjustified to exclude major mergers from the current scenarios of S0 formation and evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gunn & Gott 1972;Larson et al 1980;Moore et al 1996;Quilis et al 2000;Peng et al 2015) are often considered the main drivers of this transformation. However, numerical studies have shown that mergers, in particular major ones (mass ratios from 1:1 to 3:1), can also give rise to remnant galaxies that can be classified as S0s in terms of their morphology, structure, and scaling relations (Bekki 2001;Bekki & Couch 2011;Eliche-Moral et al 2011, 2013Borlaff et al 2014;Tapia et al 2014;Querejeta et al 2015a,b). Furthermore, Athanassoula et al (2016) have recently shown that major mergers can build up remnants of even later types (see also Springel & Hernquist 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many authors find observational evidence of a major-merger origin of many S0s at z < 1 (see Peirani et al 2009;Yang et al 2009;Hammer et al 2009aHammer et al ,b, 2012Tapia et al 2014). So, the question of whether major mergers can produce Type III S0s remains unsettled.…”
Section: Introductionmentioning
confidence: 99%